Use of sugars as alternative to chemical control: trials carried out on thrips associated with olive tree - Ilhem BOUHIDEL; Nadia LOMBARKIA; Sabah RAZI (Acta Agriculturae Slovenica, 2023)
Foliar spraying of infradoses of sugars (glucose, fructose or sucrose) induces plant resistance to pests that are particularly difficult to combat. These include thrips, which can cause flower abortion, stunting and deformation of olives, resulting in significant crop losses. Randomised block trials were conducted during three years (2017 to 2019), on two cultivars Chemlal and Sigoise, in an olive grove in Batna province (Algeria), with the aim of determining the most effective dose and type of sugar on thrips populations, and to evaluate the effectiveness of combining sugar with chemical treatment, as well as the possibility of reducing the dose of the latter. The results showed that sucrose at a concentration of 100 ppm was the most effective and that the efficacy of sucrose was higher than that of glucose and fructose, on both cultivars tested. The combination of sucrose with insecticide resulted in a synergistic effect and a higher efficacy gain than sucrose alone, and that the efficacy of the combination sucrose + insecticide at low dose D1 was identical to the combination sucrose + insecticide at recommended dose D2. It is therefore possible to reduce the chemical insecticide dose while maintaining good treatment efficacy for the control of these pests.